Humor in Nut Ped Facebook Fanpage: Linguistic Strategies and the Function of Humor - Kunwisut, Kroekkiat; Kaewjungate, Wuttinun (Journal of Arts and Thai Studies, 2024)
Objectives: The objective of this study was to study linguistic strategies for conveying humor on the Nut Ped Facebook Fanpage. and the function of language strategies that convey humor in the Nut Ped Facebook fan page Methods: The data were collected From Nut Ped Facebook Fanpage in the first half of 2023, from January 1, 2023, to June 30, 2023, with only posts that are complete in a single episode or post selected. If any posts have duplicate content, they will be analyzed only once. A total of 211 posts appeared to convey humor. Results: It was found that the linguistics strategies that convey humor can be divided into two types: (1) Verbal language strategies including the use of spoonerism, puns, homophones, hyperbole, verbal irony, unexpected utterances, and unconventional metaphors and (2) Non-verbal language strategies including the use of visual metaphors and exaggerate images. As for the function of humor that is expressed on Fanpage Facebook, there are two functions: humor helps create enjoyment, and humor is a tool to reflect society. Application of this study: This study is useful for studying the relationship between language and culture and can be used in the approach study of language used to convey humor and functions of humor in other online media continuously.